2016
DOI: 10.1186/s40795-016-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver experiences, attitudes and perceptions about feeding toddlers and preschool children in Switzerland: a qualitative study

Abstract: Background: Young children depend upon caregivers to make healthy food and beverage choices on their behalf. Research to understand caregiver perspectives may help develop interventions to improve diets and offer new insights for healthcare professionals and future nutrition studies. The main study aim was to explore caregiver feeding experiences, with a focus on portion sizes and attitudes towards beverages, for the first time in Switzerland, and contribute to the European perspective in this field. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…NVivo 11 was used for the analysis of qualitative data. A data‐driven inductive thematic analysis was conducted following methods outlined by Braun and Clarke (), which has been used as a basis for analysis in similar studies seeking to understand caregivers' feeding practices for young children (Jacquier, Gatrell, & Bingley, ). Transcripts were initially auto‐coded on the basis of the questions in the discussion guideline; these were reviewed, and three major domains specific to commercial snack foods were identified: (a) the use of commercial snack foods and beverages for children, (b) reasons for feeding commercial snack food to the children, and (c) caregiver's perception of commercial snack foods for young children.…”
Section: Methodsmentioning
confidence: 99%
“…NVivo 11 was used for the analysis of qualitative data. A data‐driven inductive thematic analysis was conducted following methods outlined by Braun and Clarke (), which has been used as a basis for analysis in similar studies seeking to understand caregivers' feeding practices for young children (Jacquier, Gatrell, & Bingley, ). Transcripts were initially auto‐coded on the basis of the questions in the discussion guideline; these were reviewed, and three major domains specific to commercial snack foods were identified: (a) the use of commercial snack foods and beverages for children, (b) reasons for feeding commercial snack food to the children, and (c) caregiver's perception of commercial snack foods for young children.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews with 19 male and female mixed income caregivers of children aged between one and five years by Jacquier, Gatrell and Bingley (2016) similarly found that caregivers' anticipation of what children would eat, influenced the amount provided. Meanwhile, Spence, Hesketh, Crawford and Campbell's (2016) interviews with 26 mothers of two-year olds found that perceived 'poor' eating and child age (younger rather than older) caused concern about the sufficiency of intake thereby leading mothers to encourage greater intake.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis was part of a wider qualitative study (and part of a doctoral research thesis) which used in-depth interviews to understand the experience, attitudes and perceptions of caregivers feeding toddlers and preschoolers (Jacquier, Gatrell, & Bingley, 2016). The wider study used indepth interviews to glean understandings about general feeding behaviours and included a M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT particular focus on the portioning of foods and beverages, along with attitudes and perceptions related to beverages in the diets of young children.…”
Section: Introductionmentioning
confidence: 99%